Profitability in the Frame of Social Entrepreneurship (Case Study on Plastic Home Waste Bank) - Luh Putu Erlina Ariya Wati; Anantawikrama Tungga Atmadja; Gede Adi Yuniarta (Universitas Pendidikan Ganesha, 2023)
Rumah Plastik is an organization with a program for recycling plastic trash that makes it valuable and economical. The research aims to find the revenue and cost structure of Rumah Plastik, the ways Rumah Plastik can maintain its profitability and thus balance both business and social goals. This was conducted in Petandakan village, District Buleleng. In this research using qualitative methods with data used are secondary data and primary data. The results of this study stated that: (1) A source of income in Rumah Plastik is obtained through the sale of plastic waste worms, furniture and education; (2) Rumah Plastik maintain their profitability by determining mission and vision in the beginning, empowerment, re-investment and sustainable to balance their business and social goals.